Análisis de la NIC 2 como instrumento de mejoramiento en la determinación del costo, para el sector industrial del cantón Quito - Osorio García, Edwin Alejandro (2016)
In this research we determine the treatment and application on the International Accounting Standard (IAS 2), with the intention of presenting new ways to improve the cost per unit and the total cost of the companies in the industry located on the province of Pichincha canton Quito. The objective consists on establishing the efficiency of the application based on the rules of inventory that over time has managed to standardize and promote useful tools for the presentation of the information in the financial statements, and that these provide reliability, transparency and certainty at the time of interpretation and decisions making business. The article proceeds to conduct field research with the tool data collection, samples such as surveys used for certain industrial enterprises, in order to determine the level of enforcement IAS 2, in the same way to develop a point to reach a better understanding of the stock treatment and to know the most appropriate way with which we can bring inventories to determine tools that allow us to save up and decisions making.